1,3-Bis(3-phenylpropyl)-1H-benzimidazol-3-ium-2-carbodithioate - Akkurt, Mehmet (International Union of Crystallography, 2008)
The title compound, C(26)H(26)N(2)S(2), was synthesized from bis[1,3-bis(3-phenylpropyl)benzimidazolidine-2-ylidene] and CS(2) in toluene. The molecular structure is composed of a benzimidazole ring system with two phenylpropyl substituents and a dithiocarboxylate group in the 2-position. The benzimidazole unit is essentially planar, with a maximum atomic deviation of 0.008 (2) Å, and makes dihedral angles of 72.72 (10) and 27.62 (12)°, with the two phenyl rings. The dihedral angle between the two phenyl rings is 55.98 (15)°. The molecular packing is stabilized by a C—H⋯S intermolecular hydrogen-bonding interaction and a C—H⋯π interaction between a benzene H atom and the phenyl ring of a neighbouring molecule.